Faktory uspešnosti sorevnovatel'noj dejatel'nosti sportsmenov v regbi-7 na osnove dannych videoanaliza (analiticeskij obzor issledovanij) - Ksenofontova, E. A.; Giyyar, M. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
In team-game sports, various software products are successfully used to assess the effectiveness and efficiency of sportsmen`s game actions, combining video analysis technologies and statistical processing of data obtained on the basis of analysis of predetermined markers that record technical and tactical actions and movements of players in competitions. This article provides an analytical review of studies devoted to the identification of informative indicators of the effectiveness of competitive activity in rugby-7, obtained on the basis of statistical processing of video analysis data.